Formulation and Evaluation of Cefixime Nanosuspension for the Enhancement of Oral Bioavailability by Solvent-Antisolvent Method and its Suitable Method Development - Mastiholimath, Vinayak Shivamurthi; Rajendra, Bhagat Ankita; Mannur, Vinodkumar Shirshalappa; Dandagi, Panchaxari Mallappa; Gadad, Anand Panchaxari; Khanal, Pukar (Indian Journal of Pharmaceutical Education and Research, 2020)
Aim: The objective of the present study was to develop and evaluate cefixime nanosuspension to enhance its oral bioavailability. Materials and Methods: The method used was solvent/ antisolvent method in which methanol and Millipore water was used as solvent and antisolvent respectively. The surfactants used for the preparation were PVP K30 and HPMC K100 which was found to be compatible in the formulation. Compatibility of the drug and drug with its excipients was found out by FTIR studies. Characterization of the optimized Cefixime Nanosuspension was carried out by particle size analysis, Differential Scanning Calorimetry, Zeta Potential, Drug content, in-vitro drug release studies, Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy(TEM). The antimicrobial activity of cefixime nanosuspension was done by Disk diffusion method against E. coli performed in nutrient agar with different concentrations of the formulation. The Minimum Inhibitory Concentration (MIC) was determined by calculating Zone of inhibition. A method was developed forcefixime nanosuspension and validated by High Performance Thin Layer Chromatography (HPTLC). Results: The optimizedcefixime nanosuspension was validated for Identification, Linearity, Specificity, Precision and Recovery. The Recovery of cefixime nanosuspension was found to be 95.57%.
Keywords: Cefixime nanosuspension; Method development; HPTLC; Solvent/ Antisolvent; method; Validation